Comparison of the replication and neutralization of different SARS‐CoV‐2 Omicron subvariants in vitro. Issue 1 (20th February 2023) - Zhang, Yaqing; Lv, Qi; Qi, Feifei; Li, Fengdi; Deng, Ran; Liang, Xujian; Liu, Mingya; Yan, Yiwei; Bao, Linlin
Abstract: Background: New Omicron subvariants are emerging rapidly from BA.1 to BA.4 and BA.5. Their pathogenicity has changed from that of wild‐type (WH‐09) and Omicron variants have over time become globally dominant. The spike proteins of BA.4 and BA.5 that serve as the target for vaccine‐induced neutralizing antibodies have also changed compared to the previous subvariants, which is likely to cause immune escape and the reduction of the protective effect of the vaccine. Our study addresses the above issues and provides a basis for formulating relevant prevention and control strategies. Methods: We collected cellular supernatant and cell lysates and measured the viral titers, viral RNA loads, and E subgenomic RNA (E sgRNA) loads in different Omicron subvariants grown in Vero E6 cells, using WH‐09 and Delta variants as a reference. Additionally, we evaluated the in vitro neutralizing activity of different Omicron subvariants and compared it to the WH‐09 and Delta variants using macaque sera with different types of immunity. Results: As the SARS‐CoV‐2 evolved into Omicron BA.1, the replication ability in vitro began to decrease. Then with the emergence of new subvariants, the replication ability gradually recovered and became stable in the BA.4 and BA.5 subvariants. In WH‐09‐inactivated vaccine sera, geometric mean titers of neutralization antibodies against different Omicron subvariants declined by 3.7 15.4‐fold compared to those against WH‐09. In Delta‐inactivated vaccine sera, geometric mean titers of neutralization antibodies against Omicron subvariants declined by 3.1 7.4‐fold compared to those against Delta. Conclusion: According to the findings of this research, the replication efficiency of all Omicron subvariants declined compared with WH‐09 and Delta variants, and was lower in BA.1 than in other Omicron subvariants. After two doses of inactivated (WH‐09 or Delta) vaccine, cross‐neutralizing activities against various Omicron subvariants were seen despite a decline in neutralizing titers. Abstract : Different Omicron subvariants were inoculated into Vero E6 cells. The cell supernatants and lysate products were collected at different time points. The supernatants were used to determine the viral loads and titers, and the cell lysate products were used to determine the viral E subgenome. Seras from macaques vaccinated with different inactivated vaccines (WH‐09 or Delta) were also collected at 14 days post infection for determination of cross‐neutralizing antibody activity. WH‐09 and Delta were used as controls.